Armies and Ecosystems in Premodern Europe The Meuse Region, 1250-1850 - Govaerts, Sander (Book collections on Project MUSE., 2021)
Using the ecosystem concept as his starting point, the author examines the complex relationship between premodern armed forces and their environment at three levels: landscapes, living beings, and diseases. The study focuses on Europe's Meuse Region, well-known among historians of war as a battleground between France and Germany. By analyzing soldiers' long-term interactions with nature, this book engages with current debates about the ecological impact of the military, and provides new impetus for contemporary armed forces to make greater effort to reduce their environmental footprint. "This is an impressive interdisciplinary study, contributing to environmental history, the history of war and historical geography. The book advances an original and intriguing argument that armed forces have had a vested interest in preserving the environments and habitats in which they operate, and have thus contributed to environmental conservation long before this became a popular cause of wider humanity. The work will provide a template for how this topic can be researched for other parts of the world or for other time periods." Peter H. Wilson, Chichele Professor of the History of War, University of Oxford.